Deconstruction of Heroism in the Film Deadpool and Wolverine (2024): Derrida’s Deconstruction Approach - Ahmad Rabani; Paramita Kusumawardhani; Fiza Asri Fauziah Habibah (ITScience (Information Technology and Science), 2026)
This study aims to explore the deconstruction of heroism in ‘Deadpool and Wolverine’ (2024) through Jacques Derrida’s theory of deconstruction. Unlike traditional superhero narratives, which emphasize virtue, order, and sacrifice, this film introduces ambiguity, irony, and moral complexity as central to the modern heroic identity. The research applies a qualitative method with a deconstructive discourse analysis approach to uncover how the film dismantles the binary oppositions between hero/antihero, good/evil, morality/amoralism, and order/chaos. The analysis reveals that both Deadpool and Wolverine are constructed as liminal figures, heroes who simultaneously embody and negate the attributes of heroism. The film subverts the myth of moral purity and exposes the fluidity of values in contemporary society. The study concludes that Derrida’s concepts of difference, binary opposition, and logocentrism effectively reveal how ‘Deadpool and Wolverine’ destabilizes the notion of fixed identity, redefining heroism as a dynamic negotiation between meaning, irony, and self- awareness.